CLINICAL CASE OF PERSISTENT ATRIAL FLUTTER IN PATIENT WITH COMORBID PATHOLOGY - Gavrilyuk, E. V.; Boeva, Y. Y.; Anyasi, I.; Maltseva, M. S.; Volkov, D .E. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Clinical case of persistent atrial flutter in combination with comorbid pathology is presented. Clinical diagnosis, choice of optimal interventional and drug therapy are discussed. Catheter ablation was considered as the optimal method for radical treatment of the atrial flutter. A modification of drug therapy is required according to the condition of the patient after the catheter ablation.